Comparison of tubeless versus tubed percutaneous nephrolithotomy - Shah, Rajiv; Lamichhane, Nirmal; K.C., Sudeep Raj (Journal of Chitwan Medical College, 2018)
Percutaneous nephrolithotomy (PCNL) is an effective treatment for large renal calculi and usually a nephrostomy tube is placed in the kidney at the end of procedure to avoid post operative complications. This is to compare the outcome of tubeless PCNL versus tubed PCNL. In a randomized prospective study of sixty-four consecutive patients were enrolled and divided into two groups; A being tubeless group and B being nephrostomy group with 32 patients in each arm divided by quota sampling restricted block method with allocation ratio of 1:1. The mean age in group A was 36.69 ± 13.65 years and in group B was 38.09 ± 13.18 years with no significant p value (p = 0.501). Duration of hospital stay in group A was 3.63 ± 1.04 days and in group B was 6.34 ± 1.71 days with a significant p value (p = 0.001). In group A 31 (96.9%) and in group B 24 (75%) cases were not transfused with blood while 1 (3.1%) and 8 (25%) cases were transfused with blood with a significant p value (p = 0.026). The post operative complications were comparable in between two groups. Therefore tubeless PCNL reduces the hospital stay and blood transfusion rate with no obvious post operative complications.